2003
DOI: 10.1177/0146167203029005006
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Black Anti-White Bias and Target Distancing Cues: Factors that Influence Perceptions of “Ambiguously Racist” Behavior

Abstract: Experiment 1 indicated that when the White supervisor's negative treatment of a Black subordinate was unconstrained, participant race had no impact on attributions. Conversely, when the treatment was constrained, Black participants reported greater racist attributions than did White participants. Experiment 2 indicated that when the supervisor reported no response or a minimal negative response (i.e., indicating that he did not support his actions) after his negative treatment of the Black subordinate, Black p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Indeed, individuals do not always agree whether specific events involve discriminatory treatment. For example, those who identify with groups that tend to be targeted by prejudice are more likely to perceive prejudice against devalued groups than members of groups that do not tend to be targeted by prejudice (e.g., Johnson, Simmons, Trawalter, Ferguson, & Reed, 2003). In addition, even when people acknowledge that their group is commonly a target of discrimination, they may or not be aware of being personally discriminated against.…”
Section: Do Members Of Devalued Groups Over-or Underestimate the Extementioning
confidence: 99%
“…Indeed, individuals do not always agree whether specific events involve discriminatory treatment. For example, those who identify with groups that tend to be targeted by prejudice are more likely to perceive prejudice against devalued groups than members of groups that do not tend to be targeted by prejudice (e.g., Johnson, Simmons, Trawalter, Ferguson, & Reed, 2003). In addition, even when people acknowledge that their group is commonly a target of discrimination, they may or not be aware of being personally discriminated against.…”
Section: Do Members Of Devalued Groups Over-or Underestimate the Extementioning
confidence: 99%
“…In a series of in-depth interviews of black respondents, they found that black males define their marketplace experiences by the presence or absence of discriminatory treatment and go on to conclude that "the black men in this sample regularly perceive encounters with market-place discrimination, and accept such treatment as an inevitable aspect of their marketing-related experiences" (Crockett et al 2003, p. 12). Furthermore, research by Johnson et al (2003) suggests that blacks are likely to consider a service failure such as the aforementioned untimely completion of an eyeglass order by a white service provider to be a purposeful and personal act of vengeance consistent with prototypical racist attitudes.…”
Section: Conceptual Background/hypothesis Developmentmentioning
confidence: 99%
“…The same failure (e.g., the wrong entrée being served in a restaurant) that a white might attribute to an innocuous situational factor (e.g., a mix-up in the kitchen) a black may attribute to racial bias on the part of the service employee and/or service firm, particularly when no other blacks are present. This correspondence bias is expected to occur since blacks do anticipate discriminatory behaviors from whites (Johnson et al 2003). Thus, the same service failure is likely to be considered far more serious by the black customer and would in all likelihood result in significantly lower levels of satisfaction towards the service provider.…”
Section: Managerial Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, targets may be more sensitive to interpersonal cues that are potentially related to prejudice (Flournoy, Prentice-Dunn, & Klinger, 2002). For example, Johnson, Simmons, Trawalter, and Ferguson (2003) found that Blacks were more likely than Whites to attribute ambiguously racist behavior to the actors' prejudiced attitudes. Similarly, target group members may hold general expectations that most interactions with majority group members are likely to include prejudice (Johnson & Lecci, 2003).…”
mentioning
confidence: 99%